Optimizing organic waste and tillage for post-mining soil rehabilitation with response surface methodology - ZAINUDIN ZAINUDIN; DYAH ROESWITAWATI; ADI SUTANTO; ALI IKHWAN; RORO KESUMANINGWATI (Smujo International, 2025)
Abstract. Zainudin, Roeswitawati D, Sutanto A, Ikhwan A, Kesumaningwati R. 2025. Optimizing organic waste and tillage for post-mining soil rehabilitation with response surface methodology. Asian J Agric 9: 739-753. Rapid urban population growth has significantly increased Municipal Organic Waste (MOW) generation, creating ecological challenges but also opportunities for sustainable land rehabilitation. In Samarinda, East Kalimantan, Indonesia, post mining degradation is a critical environmental issue that requires innovative restoration strategies. This study examined the application of MOW as a soil amendment, combined with Soil Tillage (ST), to improve chemical properties of degraded post-mining soils. A Box-Behnken design under Response Surface Methodology (RSM) was used to evaluate the effect of tillage depth (5-15 cm), Incubation Time (IT) (60-120 days) and waste dosage (20-60 t ha-1), resulting in 17 treatment combinations. The MOW included food scraps, vegetable residues, and fruit waste, excluding fish and shrimp residues. Soil analysis covered pH, Organic Carbon (OC), Total Nitrogen (TN), C/N ratio, available phosphorous (P), potassium (K), Cation Exchange Capacity (CEC), and Base Saturation (BS). The optimal condition was identified at 15 cm tillage depth, 103.48 days incubation, and 36.48 t ha-¹ waste, resulting in improvements in the characteristics of post–coal mining soil (pH: 7.43; OC: 1.26%; TN: 0.17%; C/N: 7.58; P: 36.34 ppm; K: 168.73 ppm; CEC: 15.54 me 100-¹ g; BISA: 96.61.